Kode-Kode Visual Dalam Mission: Impossible - Dead Reckoning Part One: Analisis Semiotika Deskriptif Terhadap Adegan Aksi Dan Ketegangan - Gojono, Aaron; Hidayat, Zinggara (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2026)
This study examines the visual codes in the film Mission: Impossible - Dead Reckoning Part One (2023) through John Fiske’s semiotic approach. As a spy-action film filled with high-intensity sequences, the movie presents a variety of visual signs that construct the audience’s cinematic experience. The analysis focuses on Fiske’s three levels of codes: reality, representation, and ideology complemented by verbal codes as supporting elements. Using a qualitative method with descriptive semiotic analysis, this research investigates film texts, including action scenes, dialogues, cinematography, lighting, and visual symbolism. The findings are expected to reveal how visual elements function not merely as aesthetic entertainment but also as tools for constructing ideological meanings related to heroism, technological domination, and global surveillance. The novelty of this research lies in its emphasis on visual codes within action films, an area often overlooked, thereby contributing to film and visual communication studies and providing valuable insights for filmmakers in designing meaningful action sequences.